The Microcomputer, New Publishing Technology, And The Impact on The Editor's Role - Thomas W. Knecht (Journal of Applied Communications, 1987)
Those working in editing and publishing have seen many changes over the past decade - changes in the way text is handled, artwork prepared and type set. Most of these changes have been brought about by the introduction of microcomputers into the work areas of editors, typographers, artists, and secretaries.